KERAJINAN SULAMAN KARAWO SEBAGAI DAYA TARIK WISATA MINAT KHUSUS DI PROVINSI GORONTALO (KASUS SENTRA KERAJINAN SULAMAN KARAWO) - Anggraeni M.S Lagalo (Program Studi S1 Pariwisata, Universitas Muhammadiyah Gorontalo, 2018)
Special Interest Tourism (SIT) is defined as travelling with the primary motivation of practicing or enjoying a special interest. This can include unusual hobbies, activities, themes or attractions which tend to atract visitors. This research aims at analyzing the strategy of developing Karawo embroidery as a special interest tourism in Gorontalo. A case study conducted in Karawo embroidery center. Moreover, Karawo embroidery, one of traditional cultural activities in Gorontalo which has been inherited from generation to generation, has gained great attention and effort from the local government to attract visitors to come, yet the report said there is no increase in visitors. Therefore, in this case, the writer focuses on the strategy to develop Karawo embroidery center so as to attract more visitors or tourists to come. This research has three main goals to achieve. 1) Gaining perception from the local or foreign tourists about Karawo, 2) Identifying obstacles faced in developing Karawo embroidery as special interest tourism, 3) Formulating the strategy in developing Karawo embroidery as special interest tourism in Gorontalo. Moreover, this research conducted by using mixed method. However, qualitative descriptive method was primarily applied in this research. While quantitative was applied to attain supporting data. Furthermore, results show that Karawo embroidery, overall, is considered very attractive. According to the SWOT analysis, the strategy chosen to be applied is by combining Strength and Opportunity (SO) or aggressive strategy. This was based on the Cartesian diagram mapping which was created by applying weighted score on each factor.